Bacterial microbiota from the gut of Rhodnius ecuadoriensis, a vector of Chagas disease in Ecuador's Central Coast and Southern Andes - Villacís, Juan F.; López-Rosero, Andrea; Bustillos, Juan José; Cadena, Matías; Yumiseva, César A.; Grijalva, Mario J.; Villacís, Anita G. (Frontiers in Microbiology, 2024)
Chagas disease is a neglected tropical disease caused by the parasite Trypanosoma cruzi that is transmitted mainly by the feces of infected Triatomines. In Ecuador the main vector is Rhodnius ecuadoriensis which is distributed in several provinces of the country. More than 40% of these insects in the wild have T. cruzi as part of their intestinal microbiota. For this reason, the objective of this research was to characterize the intestinal bacterial microbiota of R. ecuadoriensis. The methodology used was based on the DNA extraction of the intestinal contents from the wild collected insects (adults and nymphs V), as well as the insects maintained at the insectary of the CISeAL. Finally, the samples were analyzed by metagenomics extensions based on the different selected criteria. The intestinal microbiota of R. ecuadoriensis presented a marked divergence between laboratory-raised and wild collected insects. This difference was observed in all stages and was similar between insects from Loja and Manabí. A large loss of microbial symbionts was observed in laboratory-raised insects.